Chemoenzymatic radiosynthesis of 2-deoxy-2-[18F]fluoro-d-trehalose ([18F]-2-FDTre): A PET radioprobe for in vivo tracing of trehalose metabolism. (15th January 2019) - Peña-Zalbidea, Santiago; Huang, Ashley Y.-T.; Kavunja, Herbert W.; Salinas, Beatriz; Desco, Manuel; Drake, Christopher; Woodruff, Peter J.; Vaquero, Juan J.; Swarts, Benjamin M.
Abstract: Trehalose analogues bearing fluorescent and click chemistry tags have been developed as probes of bacterial trehalose metabolism, but these tools have limitations with respect to in vivo imaging applications. Here, we report the radiosynthesis of the 18 F-modified trehalose analogue 2-deoxy-2-[ 18 F]fluoro-d -trehalose ([ 18 F]-2-FDTre), which in principle can be used in conjunction with positron emission tomography (PET) imaging to allow in vivo imaging of trehalose metabolism in various contexts. A chemoenzymatic method employing the thermophilic TreT enzyme from Thermoproteus tenax was used to rapidly (15–20 min), efficiently (70% radiochemical yield; ≥ 95% radiochemical purity), and reproducibly convert the commercially available radiotracer 2-deoxy-2-[ 18 F]fluoro-d -glucose ([ 18 F]-2-FDG) into the target radioprobe [ 18 F]-2-FDTre in a single step; both manual and automated syntheses were performed with similar results. Cellular uptake experiments showed that radiosynthetic [ 18 F]-2-FDTre was metabolized by Mycobacterium smegmatis but not by various mammalian cell lines, pointing to the potential future use of this radioprobe for selective PET imaging of infections caused by trehalose-metabolizing bacterial pathogens such as M. tuberculosis . Graphical abstract: Highlights: 18 F-2-FDTre was produced from commercially available 18 F-2-FDG in 15 min using heat-stable TreT enzyme. The synthesis proceeded with high radiochemical yield (70%) and purity (≥95%). The synthesis was done both manually and on an automated radiosynthesis module. 18 F-2-FDTre was metabolized by mycobacteria but not mammalian cells.